Sympathetic overdrive and unrestrained adipose lipolysis drive alcohol-induced hepatic steatosis in rodents - Chunxue Zhou; Henry H. Ruiz; Li Ling; Giulia Maurizi; Kenichi Sakamoto; Claudia G. Liberini; Ling Wang; Adrien Stanley; Hale E. Egritag; Sofia M. Sanz; Claudia Lindtner; Mary A. Butera; et al. (Molecular Metabolism, 2023)
Objective: Hepatic steatosis is a key initiating event in the pathogenesis of alcohol-associated liver disease (ALD), the most detrimental organ damage resulting from alcohol use disorder. However, the mechanisms by which alcohol induces steatosis remain incompletely understood. We have previously found that alcohol binging impairs brain insulin action, resulting in increased adipose tissue lipolysis by unrestraining sympathetic nervous system (SNS) outflow. Here, we examined whether an impaired brain–SNS–adipose tissue axis drives hepatic steatosis through unrestrained adipose tissue lipolysis and increased lipid flux to the liver. Methods: We examined the role of lipolysis, and the brain–SNS–adipose tissue axis and stress in alcohol induced hepatic triglyceride accumulation in a series of rodent models: pharmacological inhibition of the negative regulator of insulin signaling protein-tyrosine phosphatase 1β (PTP1b) in the rat brain, tyrosine hydroxylase (TH) knockout mice as a pharmacogenetic model of sympathectomy, adipocyte specific adipose triglyceride lipase (ATGL) knockout mice, wildtype (WT) mice treated with β3 adrenergic agonist or undergoing restraint stress. Results: Intracerebral administration of a PTP1b inhibitor, inhibition of adipose tissue lipolysis and reduction of sympathetic outflow ameliorated alcohol induced steatosis. Conversely, induction of adipose tissue lipolysis through β3 adrenergic agonism or by restraint stress worsened alcohol induced steatosis. Conclusions: Brain insulin resistance through upregulation of PTP1b, increased sympathetic activity, and unrestrained adipose tissue lipolysis are key drivers of alcoholic steatosis. Targeting these drivers of steatosis may provide effective therapeutic strategies to ameliorate ALD.